Intra-laboratory comparison of four analytical platforms for lipidomic quantitation using hydrophilic interaction liquid chromatography or supercritical fluid chromatography coupled to quadrupole - time-of-flight mass spectrometry - Chocholoušková, Michaela; Wolrab, Denise; Jirásko, Robert; Študentová, Hana; Melichar, Bohuslav; Holčapek, Michal (Talanta, 2021)
The lipidomic research is currently devoting considerable effort to the harmonization that should enable the generation of comparable and accurate quantitative lipidomic data across different laboratories and regardless of the mass spectrometry-based platform used. In the present study, we systematically investigate the effects of the experimental setup on quantitative lipidomics data obtained by two lipid class separation approaches, hydrophilic interaction liquid chromatography (HILIC) and ultrahigh-performance supercritical fluid chromatography (UHPSFC), coupled to two different quadrupole - time of flight (QTOF) mass spectrometers from the same vendor. This approach is applied for measurements of 268 human plasma samples of healthy volunteers and renal cell carcinoma patients resulting in four data sets. We investigate and visualize differences among these data sets by multivariate data analysis methods, such as principal component analysis (PCA), orthogonal partial least square discriminant analysis (OPLS-DA), box plots, and logarithmic correlations of molar concentrations of individual lipid species. The results indicate that even measurements in the same laboratory for the same samples using different analytical platforms may yield slight variations in the molar concentrations determined. The normalization to a reference sample with defined lipid concentrations can further diminish these small differences, resulting in highly homogenous molar concentrations of individual lipid species. This strategy indicates a potential approach towards the reporting of comparable quantitative results independent from the quantitative approach and mass spectrometer used, which is important for a wider acceptance of lipidomics data in various biomarker inter-laboratory studies and ring trials.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; laboratoře; Chromatography, Supercritical Fluid; Lipidomics; vysokoúčinná kapalinová chromatografie; superkritická fluidní chromatografie; lidé; Chromatography, High Pressure Liquid; Chromatography, Liquid; Hydrophobic and Hydrophilic Interactions; lipidomika; Laboratories; chromatografie kapalinová; hydrofobní a hydrofilní interakce; Humans